Cross and Tapper on evidence - Tapper, Colin; Cross, Rupert, Sir, 1912-1980. (Oxford : Oxford University Press, 2010)
"The most authoritative and respected textbook in the field, Cross & Tapper on Evidence has, over successive editions, acquired a justly de served reputation as a classic of legal literature. The twelfth edit ion reflects recent changes and developments in an extremely fast-movin g and important subject. It continues to provide thorough coverage and analysis of the ongoing impact of the Criminal Justice Act 2003, with a particular focus in this edition on developments relating to evidence of character. The ways in which the jurisprudence of the European Cou rt of Human Rights continues to penetrate English law are also fully ev aluated. The wide coverage of overseas materials from the principal common law jurisdictions is retained. This comparative material provid es an excellent basis for the critical analysis and appraisal of Englis h law. Cross & Tapper remains the most thorough text on the law of evi dence available, and is suitable for use by students and practitioners alike"--
Includes bibliographical references and index.
Keywords: Evidence (Law) -- England; Evidence (Law) -- Wales